Trophic interactions in soil micro‐food webs drive ecosystem multifunctionality along tree species richness - Xiuzhen Shi; Nico Eisenhauer; Josep Peñuelas; Yanrong Fu; Jianqing Wang; Yuxin Chen; Shengen Liu; Lulu He; Manuel Esteban Lucas‐Borja; Liyan Wang; Zhiqun Huang (Global Change Biology, 2024)
Rapid biodiversity losses under global climate change threaten forest ecosystem functions. However, our understanding of the patterns and drivers of multiple ecosystem functions across biodiversity gradients remains equivocal. To address this important knowledge gap, we measured simultaneous responses of multiple ecosystem functions (nutrient cycling, soil carbon stocks, organic matter decomposition, plant productivity) to a tree species richness gradient of 1, 4, 8, 16, and 32 species in a young subtropical forest. We found that tree species richness had negligible effects on nutrient cycling, organic matter decomposition, and plant productivity, but soil carbon stocks and ecosystem multifunctionality significantly increased with tree species richness. Linear mixed‐effect models showed that soil organisms, particularly arbuscular mycorrhizal fungi (AMF) and soil nematodes, elicited the greatest relative effects on ecosystem multifunctionality. Structural equation models revealed indirect effects of tree species richness on ecosystem multifunctionality mediated by trophic interactions in soil micro‐food webs. Specifically, we found a significant negative effect of gram‐positive bacteria on soil nematode abundance (a top‐down effect), and a significant positive effect of AMF biomass on soil nematode abundance (a bottom‐up effect). Overall, our study emphasizes the significance of a multitrophic perspective in elucidating biodiversity‐multifunctionality relationships and highlights the conservation of functioning soil micro‐food webs to maintain multiple ecosystem functions.